Konsep Pendidikan Multikultural di Madrasah (Studi Lapangan di MAN 2 Model Medan) - Asyikin, Nurul; Salmah, Nur; Hanum OK, Azizah (TABYIN: JURNAL PENDIDIKAN ISLAM, 2022)
This article is to find out how the implementation of the concept of multicultural education in Madrasah, especially at MAN 2 Model Medan, what the concept of multicultural education has been done in the madrasah. So that from the concept of multicultural education that has been applied, it is hoped that students in the madrasa can understand, practice and realize a diversity in the community environment and cause an attitude of patriotism, tolerance, and mutual respect for others, even though different ethnicities, cultures, and even religions.